Atlas of Interactions Between Decoration Proteins and Major Capsid Proteins of Coliphage N4 - Klem McJarrow-Keller; Alice-Roza Eruera; Alexander J. M. Crowe; Rosheny Kumaran; Jaekyung Hyun; Mihnea Bostina (Viruses)
Coliphage N4 is a representative species of the Schitoviridae family of bacteriophages. Originally structurally studied in 2008, the capsid structure was solved to 14 Å to reveal an interesting arrangement of Ig-like decoration proteins across the surface of the capsid. Herein, we present a high-resolution N4 structure, reporting a 2.45 Å map of the capsid obtained via single particle cryogenic-electron microscopy. Structural analysis of the major capsid proteins (MCPs) and decoration proteins (gp56 and gp17) of phage N4 reveals a pattern of interactions across the capsid that are mediated by structurally homologous domains of gp17. In this study, an analysis of the complex interface contacts allows us to confirm that the gp17 Ig-like decoration proteins of N4 are likely employed by the virus to increase the capsid’s structural integrity.